Yield Potential of Ten Peanut Introgression Lines derived from Crosses between Arachis cardenassii and A. hypogaea - AHMAD RIDUAN; SUDARSONO SUDARSONO (HAYATI Journal of Biosciences, 2005)
Diploid species of peanut (Arachis cardenasii) showed no symptoms of PStV infection when mechanically inoculated with PStV. Some introgression lines derived from A. cardenasii and A. hypogaea hybridization have been introduced to Indonesia. Evaluation of their adaptability and yield potential were necessary before pursuing further utilization of these introgression lines. The objectives of this research were to determine yield potential of the introgression lines of peanut in green house and field conditions and to evaluate incidence of PStV infection in the field. Peanut plants were grown in the green house and in the field according to standard procedures for raising peanut. Results of the experiments showed that growth and developmental characters of the tested lines were similar between field and green house grown plants. The introgression lines generally exhibited higher secondary branches and longer to flower and harvest as compared to peanut cv. Gajah and Kelinci. The NC-CS30 line was identfied as having higher yield and bigger seed size as compared to standard peanut cultivars (Gajah and Kelinci). Therefore, NC-CS30 germplasm may be further developed as commercial peanut cultivar or be used as donor for peanut breeding in Indonesia.